ANALISIS PENGARUH KARAKTRISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO PERUSAHAAN (Studi Empiris Pada Perusahaan-Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2012-2015) - Khotib Zaenal Mustofa, 13.05.52.0165; Lisiantara, G. Anggana (Students Journal of Accounting and Banking, 2017)
This research aims to examine and analyse empirical evidence about the influence of karaktristik company and corporate governance risk disclosure against the companies in manufacturing companies. The characteristics of companies that are used in this research is the level of profitability, the companys size, the level of liquidity, stock ownership structure, the size of the Board of Commissioners and the expertise of the audit committee the audit committee meeting frequency. Method of sampling using a purposive sampling with a period of 2012-2015 years of research. As many as 94 registered manufacturing company BEI (Indonesia stock exchange) be used as a sample in this research. Stakeholder theory is used to describe the relationships between variables. Risk disclosure in this study using a content analysis based on identifying sentences risk disclosure in reports annual report. Statistical methods are used to test the hypothesis is multiple regression analysis. The results of this study suggest that public ownership structure positive effect significantly to levels of risk disclosure company. While the companys size, profitability, liquidity, the expertise of the audit committee of the Board of Commissioners, the size and frequency of meetings of the audit committee of influential positive and insignificant against the disclosure of the risks of the company.Keywords:Â Risk Disclosure, Stakeholder Theory, Profitability Level, Firm Size, Liquidity Level, Public Shareholding Structure, Board Size, Audit Committee Expertise, and Frequency of Meetings of The Audit Committee